When Noise meets Chaos: Stochastic Resonance in Neurochaos Learning. (November 2021) - N.B., Harikrishnan; Nagaraj, Nithin
Abstract: Chaos and Noise are ubiquitous in the Brain. Inspired by the chaotic firing of neurons and the constructive role of noise in neuronal models, we for the first time connect chaos, noise and learning. In this paper, we demonstrate Stochastic Resonance (SR) phenomenon in Neurochaos Learning (NL). SR manifests at the level of a single neuron of NL and enables efficient subthreshold signal detection. Furthermore, SR is shown to occur in single and multiple neuronal NL architecture for classification tasks — both on simulated and real-world spoken digit datasets, and in architectures with 1 D chaotic maps as well as Hindmarsh–Rose spiking neurons. Intermediate levels of noise in neurochaos learning enable peak performance in classification tasks thus highlighting the role of SR in AI applications, especially in brain inspired learning architectures.